Políticas de estado e correlação de forças locais: hegemonia e contradição na expressão real das Instituições Federais de Educação Profissional. - Oliveira, Elenilce Gomes de (2007)
This project is about the changes in the Brazilian professional education, related to the pedagogical-curriculum organization, management and financing in the federal centers of technological education, above all in the period of 1996-2006. The purpose is to emphasize the politico-economical and social supremacy articulation − agglutinated to the ambit of the Brazilian State in the public professional education − analyzing how the federal educational institutions deal with these interests. The following up related to the politics implied in advancement and retrocession, leading to some questions: How do the politico-economical and social interests agglutinated to the ambit of the Brazilian State spread into public professional education? How do the federal educational institutions deal with these interests? It has been assumed in this the theoric-referential “gramsciano” based above all in the categories amplified state, passive revolution supremacy and ideology. A federal public institution of professional education has been approached, where twenty-two people – teachers and civil servants, were interviewed in order to find out how the people deal with the changes. It has been pointed out the claim of the dominated trying to decrease the conflicts and contradictions that are part of the base in the irregular structure of the capitalistic society. Considering the context where the politics to professional education and its interface with the international members occur, which means the rejection to the national-developmental state, the conjugation of the neo-liberalism and third path. The plans and the programs in the federal context have been examined and finally how these politics are retained in the schooling ambit and in the end has been analyzed out in one hand the political society use of he legislation where the state drives to a passive educational revolution, and in the other hand the building of the consensus of the civil society, resulting in creating favor or against changes to the employees, that are connected and influence by themselves, according to the correlation of the social power.